Aspecto Técnicos de las Acciones Nacionales de Mitigación Apropiada (NAMA) para los sistemas ganaderos en la región de América Latina y el Caribe - Otárola, M.; Sepúlveda, Claudia J.; Villanueva, C.; Solano, C.; Martínez Barón, Deissy; Arango, Jacobo; Román Cuesta, Rosa María (Centro Agronómico Tropical de Investigación y Enseñanza, 2021)
This document provides important information about the main technical aspects of livestock NAMAs, as well as the challenges they face and some recommendations that will help them to improve. It is focused in nine countries of the LAC region(Mexico, the Dominican Republic, Guatemala, Honduras, Costa Rica, Colombia, Argentina, Uruguay and Paraguay); but more specifically in five of them, where climate actions in the cattle sector are best documented (Costa Rica, Colombia, Guatemala, Honduras and Uruguay). Based on the key aspects of organization, logic and mitigation goals, the most relevant technical aspects of the NAMA proposals were reviewed to suggest guidelines and orientation for the technical design, and for the implementation of those initiatives. The study was developed between November 2018 and February 2019, by reviewing and analyzing secondary information and consulting(remotely) with key informants from each country evaluated.